Validation of the Italian version of the intuitive exercise scale: a four-factor structure in the general population - Paolo Mancin; Marta Ghisi; Tatiana Moro; Silvia Cerea (Eating and Weight Disorders)
Abstract Purpose Intuitive exercise may foster healthier engagement in physical activity, leading to enhanced well-being and more intuitive eating habits. The Intuitive Exercise Scale (IEXS) was originally developed to assess this construct in English speakers. The IEXS is composed of four scales addressing distinct facets of intuitive exercise: emotional exercise, body trust, exercise rigidity, mindful exercise. The present study aimed to validate an Italian translation of the IEXS, exploring its factorial structure, invariance, internal consistency, and convergent validity. Methods A sample of 1140 women and men (age: M = 45.25, SD = 11.64, range 22–76 years) was recruited from the Italian general population; 61.8% were physically active. Inclusion criteria were being an Italian native speaker and being at least 18 years. The sample was randomly split in two equal halves for the Exploratory Factor Analysis (n = 570; women: 50%; physically active: 61.8%) and the Confirmatory Factor Analysis (n = 570; women: 50%; physically active: 61.8%). Multi-group confirmatory factor analyses were performed to assess invariance among women and men and physically and non-physically active individuals. McDonald’s omega was used to assess internal consistency. Pearson’s correlations were utilized to assess convergent validity. Results The Italian IEXS replicated a four-factor structure and showed good invariance among women and men. Invariance among physically and non-physically active individuals was only partially supported. Excellent internal consistency and adequate convergent validity were achieved. Conclusions The IEXS demonstrated to be a valid measure to examine intuitive exercise in the Italian population, replicating and expanding the findings of the English version. Level of evidence Level V, Cross-sectional, Psychometric study.